PENGARUH PENGGUNAAN PUPUK ORGANIK TERHADAP PERTUMBUHAN TANAMAN Indigofera zollingeriana: THE EFFECT OF ORGANIC FERTILIZER ON THE GROWTH OF Indigofera zollingeriana - Abdullah Shidiq Nurfaiz; Catur Suci Purwati; Yahya Ibadurrahman (Universitas Boyolali, 2026)
Organic fertilizer is the result of microbiological activity in decomposing organic matter, and has slow release properties (slowly available) but can be available longer in the soil than inorganic fertilizers. The application of organic fertilizer also plays a role in increasing soil microbial activity, suppressing plant diseases, and increasing nutrient absorption efficiency, thereby maintaining or increasing soil and plant productivity. Organic fertilizer can be produced from agricultural and livestock waste through fermentation or composting, resulting in liquid or solid organic fertilizer. This type of research is a field experiment aimed at determining the effect of liquid organic fertilizer (POC) on the growth of Indigofera zollingeriana plants. The variables observed were branch growth, number of new shoots, leaves, and plant height. Based on the results of research on the effect of liquid organic fertilizer (POC) on the growth of Indigofera zollingeriana at various treatment doses (10 ml, 20 ml, 30 ml, and 40 ml), it can be concluded that the application of liquid organic fertilizer on the growth of Indigofera zollingeriana affects the growth of the number of leaves but does not affect the growth of the number of shoots, branches, and plant height.